The Molecular Chaperone Mechanism of the C-Terminal Domain of Large-Size Subunit Catalases - Teresa Nava-Ramírez; Sammy Gutiérrez-Terrazas; Wilhelm Hansberg (MDPI AG, 2023)
Large-size subunit catalases (LSCs) have an additional C-terminal domain (CT) that is structurally similar to Hsp31 and DJ-1 proteins, which have molecular chaperone activity. The CT of LSCs derives from a bacterial Hsp31 protein. There are two CT dimers with inverted symmetry in LSCs, one dimer in each pole of the homotetrameric structure. We previously demonstrated the molecular chaperone activity of the CT of LSCs. Like other chaperones, LSCs are abundant proteins that are induced under stress conditions and during cell differentiation in bacteria and fungi. Here, we analyze the mechanism of the CT of LSCs as an unfolding enzyme. The dimeric form of catalase-3 (CAT-3) CT (TDC3) of Neurospora crassa presented the highest activity as compared to its monomeric form. A variant of the CAT-3 CT lacking the last 17 amino acid residues (TDC3Δ17aa), a loop containing hydrophobic and charged amino acid residues only, lost most of its unfolding activity. Substituting charged for hydrophobic residues or vice versa in this C-terminal loop diminished the molecular chaperone activity in all the mutant variants analyzed, indicating that these amino acid residues play a relevant role in its unfolding activity. These data suggest that the general unfolding mechanism of CAT-3 CT involves a dimer with an inverted symmetry, and hydrophobic and charged amino acid residues. Each tetramer has four sites of interaction with partially unfolded or misfolded proteins. LSCs preserve their catalase activity under different stress conditions and, at the same time, function as unfolding enzymes.